Self-reflection Levels in Learning among the Medical Students at Faculty of Medicine, Universitas Swadaya Gunung Jati, Cirebon, Indonesia - Faturrahman, Farhan Raka; Permatasari, Tissa Octavira; Meidianawaty, Vivi (GHMJ (Global Health Management Journal), 2024)
Background: Self-reflection is one of the most important characteristics that students, especially medical students, need to have during their studies. With the challenges across medical doctor programs, students need to have adequate self-assessment skills. Aims: This study aims to determine the level of self-reflection skills in students of the Faculty of Medicine, Universitas Swadaya Gunung Jati at the academic and professional stages. Methods: This is a descriptive observation research with 418 respondents consisting of students at the academic and professional stages. This study used a reflection-in-learning questionnaire that has been adapted into Indonesian to assess the level of student self-reflection with the results are divided into six levels of indicators: "Null", "Minimal", "Restricted", "Partial", "Sufficient", and "Maximal". Results: The results of this study indicate that the highest level of student self-reflection is in the "Sufficient" indicator (45%), followed by the "Maximal" indicator (34.2%), the "Partial" indicator (18.7%), the "Restricted" indicator (1.9%), the "Minimal" indicator (0.2%), and the "Null" indicator (0%). Conclusion: This study concludes that the level of self-reflection skills in students of the Faculty of Medicine, Universitas Swadaya Gunung Jati, both at the academic and professional stage, is classified as a level of ability that is quite good.   Received: 25 September 2024  |  Reviewed: 17 October 2024  |  Revised: 05 November 2024  |  Accepted: 30 November 2024.